Medición del grado de satisfacción de los clientes de la unidad educativa fiscomisional Fray Cristóbal Zambrano del cantón Saraguro, provincia de Loja, para el año 2016 - Sánchez Arias, Luis Vicente (2017)
The development of this thesis entitled "MEASUREMENT OF THE DEGREE OF SATISFACTION OF CUSTOMERS OF THE FISCOMISIONAL EDUCATIONAL UNIT FRAY CRISTOBAL ZAMBRANO DEL CANTÓN SARAGURO, PROVINCE OF LOJA, FOR THE YEAR 2016", was carried out with the aim of measuring the degree of satisfaction Of the internal and external actors in order to determine if the standards for this type of institution are being met. With the information obtained, it was possible to generate measures or actions to be taken which can improve the level of education, since not only the academic level but also the working environment and the physical space of the institution were measured. From all points of view, the customer decides what product or service he or she wants, for this reason customer satisfaction is the most important thing. At the institutional level, measuring customer satisfaction is beneficial because whoever is satisfied with consuming or acquiring a good or because it is fulfilling its mission. In this case the parents are the clients to whom through their children the educational service is offered to them and the students the consumers who communicate their parents regarding the satisfaction of the learning received in the Educational Unit. As an initial step for the development of the present work, the use of methods such as deductive was considered, which was used for the approach of the respective hypothesis, the inductive allowed to study first those general aspects, then to reverse them in principles applicable to reality Of the researched site, the statistician facilitated the representation of the information obtained in tables and graphs, the synthetic analytic allowed to summarize, analyze, describe and present the required information, which was organized according to the theoretical explanatory needs, for the purpose To give a revealing answer to the problem investigated; As well as some techniques such as observation and interview, which allowed to know in a verified way the problematic investigated. With this information, we conclude that the level of satisfaction (60%) in parents does not reach a significant level, a measure that was carried out considering factors such as institutional philosophy, development of academic, cognitive and evaluative skills, relationship Teacher-student, extra-class activities, conflict resolution and administrative procedures. In such considerations a plan of improvement to the customer service of the Educational Unit Fiscomisional "Fray Cristóbal Zambrano" is proposed.